Roles of microRNAs in abiotic stress response and characteristics regulation of plant - Zhang, Feiyan; Yang, Jiangwei; Zhang, Ning; Wu, Jiahe; Si, Huaijun (Frontiers in Plant Science, 2022)
MicroRNAs (miRNAs) are a class of non-coding endogenous small RNA (long 20-24 nucleotides) that negatively regulate eukaryotes gene expression at post-transcriptional level via cleavage or/and translational inhibition of targeting mRNA. Based on the diverse roles of miRNA in regulating eu-karyotes gene expression, research on the identification of miRNA target genes has been carried out, and a growing body of research has demonstrated that miRNAs act on target genes and are involved in various biological functions of plants. It has an important influence on plant growth and development, morphogenesis and stress response. Recent case studies indicate that miRNA-mediated regulation pattern may improve agronomic properties and confer abiotic stress resistance of plants, so as to en-sure sustainable agricultural production. In this regard, we focus on the recent updates on miRNAs and their targets involved in responding to abiotic stress including low temperature, high temperature, drought, soil salinity and heavy metals, as well as plant growing development. In particular, this review highlights the diverse functions of miRNAs on achieving the desirable agronomic traits in important crops. Herein, the main research strategies of miRNAs involved in abiotic stress resistance and crop traits improvement were summarized. Furthermore, the miRNA-related challenges and future perspectives of plants have been discussed. MiRNA-based research lays the foundation for exploring miRNA regulatory mechanism, which aims to provide insights into a potential form of crop im-provement and stress resistance breeding.